Analisis Maslahah Najmuddin al-Thufi Terhadap Menajemen Menghadapi Tekanan Pertanyaan 'Kapan Menikah': Najmuddin al-Thufi's Maslahah Analysis of Managing the Pressure of the Question 'When to Marry' - Sugitanata, Arif; Intan Hidayah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
This research focuses on the social and cultural dynamics related to the pressure of the question